Drivers of Purchase Intention in Cross-Border E-Commerce: The Role of Platform Quality and Trust - Melissa; Nasar Buntu Laulita (Journal of Enterprise and Development (JED), 2024)
Purpose: The purpose of this study is to explore the factors influencing cross-border e-commerce consumers, particularly platform quality aspects such as information quality, system quality, and service quality, on purchase intention, with trust as a mediating factor.Method: This research employs quantitative methods. The measurement and structural models were evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS v.3.9 application to test the hypotheses based on data from a total of 280 respondents.Result: The study found that information quality, system quality, and service quality in cross-border e-commerce significantly influence trust and purchase intention. Customer trust mediates the effects of information quality and service quality on purchase intention, but it does not significantly mediate the effect of system quality.Practical Implications for Economic Growth and Development: This research provides strategic insights for cross-border e-commerce companies to enhance platform quality and consumer trust, which can lead to market expansion, promote digital economic growth, and support global e-commerce development.